Status of needs, development and evaluation in teacher training in ICT: Extremadura - Isabel Cuadrado Gordillo (ADIDE Federación, 2008)
The new technologies of Information and Communication have had a presence and use of over twenty years at school now. The portrait of the first computers' classroom where a teacher would teach the students a coded language to deal with files is no longer real. The main drawback for the widespread of the use of these technologies as a tool and supporting material was once the need to commute to overworked specific computers' classrooms. This obstacle has been definitely removed by the systematic inclusion of computers in every classroom.